Decellularized extracellular matrix scaffolds: Recent trends and emerging strategies in tissue engineering - Xuewei Zhang (KeAi Communications Co., Ltd., 2022)
The application of scaffolding materials is believed to hold enormous potential for tissue regeneration. Despite the widespread application and rapid advance of several tissue-engineered scaffolds such as natural and synthetic polymer-based scaffolds, they have limited repair capacity due to the difficulties in overcoming the immunogenicity, simulating in-vivo microenvironment, and performing mechanical or biochemical properties similar to native organs/tissues. Fortunately, the emergence of decellularized extracellular matrix (dECM) scaffolds provides an attractive way to overcome these hurdles, which mimic an optimal non-immune environment with native three-dimensional structures and various bioactive components. The consequent cell-seeded construct based on dECM scaffolds, especially stem cell-recellularized construct, is considered an ideal choice for regenerating functional organs/tissues. Herein, we review recent developments in dECM scaffolds and put forward perspectives accordingly, with particular focus on the concept and fabrication of decellularized scaffolds, as well as the application of decellularized scaffolds and their combinations with stem cells (recellularized scaffolds) in tissue engineering, including skin, bone, nerve, heart, along with lung, liver and kidney.